Традиція, образ і мислення автора “Слова о полку Ігоревім” - Салевич, П. (Слово і Час, 2018)
У статті автор наголошує на необхідності переосмислити невідповідне сприйняття української
літератури XI – XIII ст., некоректно означеної як двовірної. Уперше досліджено проблему традиції,
образ автора та особливості авторського мислення у “Слові”. Традицію автора, його художню
техніку з мовою і словом, що відтворює дії жерця в ритуальному обряді, а також мисленнєві
конструкції (міфологічні мотиви, ритуали, символи, міфологічні коди тексту “Слова”) вияснено
як елементи системно-комплексного міфоепічного мислення. The study emphasizes the need of rethinking the controversial perception of Ukrainian literature of
the 11th–13th centuries, based on the notion of so-called ‘dual-faith’. It offers an analysis of the tradition,
images and peculiarities of the author’s thinking in “The Tale...”. The facts proving the existence of the
literary pagan tradition in the old Ukraine in the 11th and the 12th centuries and evidence of struggle
against the Ukrainian cultural pagan tradition in the 16th and 18th centuries have been provided.
In the first part of the study the researcher speaks of the close connection between the traditions
characteristic for the author of “The Tale” and the Ukrainian mythological tradition, assuming that the
songwriter Boyan was its most famous representative in the 11th century. The second part of the
study offers an attempt of modeling the mythological image of the author, describing his basic thought
structures, in particular, mythological motifs, as well as other pagan ethnic codes and symbols present
in the text of “The Tale...”. The researcher aims to reveal the systemic links between these elements
and characterizes them as a vast spectrum representing the Ukrainian mythopoetic world and its laws.
The facts are given in the form of an integral hierarchical model, preserving and actualizing the deep,
sacred meanings and values of the Ukrainian people, determining their informational and semiotic
space. The language and its words within the artistic technique of the author imitate the actions in
the pagan sacrificial ritual. Thus various mythological codes of “The Tale...” have been interpreted as
elements of systemic and complex mythoepic author’s thinking. В статье указывается на необходимость переосмысления
несоответствующего восприятия украинской литературы
XI – XIII вв., некорректно названной двоеверной. Впервые
рассмотрен вопрос традиции, образа и особенностей авторского
мышления в “Слове”. Традиция автора, его художественная
техника с языком и словом, которая воспроизводит действия
жреца в ритуальном обряде, а также мыслительные конструкции –
мифологические мотивы, ритуалы, символы – и другие разного
рода мифологические коды текста “Слова” выяснены как элементы
системно-комплексного мифоэпического мышления.
Ключевые слова: традиция автора, певец Боян, образ автора,
авторское мышлениe, заговоры, мотив, медиация, образ мирового
дерева, примoвка, ритуал, тотем медведя, языческий культ рода,
антропоморфное, анимистическое и магическое представление
о мире.